Positive impact of patient participation in arthroscopic anterior cruciate ligament reconstruction surgery on clinical and functional outcomes, rehabilitation and patient satisfaction - Burak Çakar; Erdal Uzun; Wubulıkasımu Xıaokaıtı; Sebati Başer Canbaz; Ahmet Güney (BMC Musculoskeletal Disorders)
Abstract Background This study aimed to evaluate the effect of patient participation on clinical and functional outcomes, satisfaction, and compliance with postoperative rehabilitation in patients undergoing surgery for anterior cruciate ligament (ACL) injury. Methods Sixty-one patients who underwent isolated ACL reconstruction (ACLR) were included. Thirty patients in the participation group were shown the arthroscopy screen and allowed to communicate with the surgeon during surgery. For clinical and functional evaluation, knee joint range of motion (ROM), International Knee Documentation Committee Subjective Knee Form (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS), Lysholm Knee Scoring Scale (LKSS), Short Form-36 (SF-36) score, and Tegner Activity Scale (TAS), were used. The Pain Quality Assessment Scale was used to assess pain. Additionally, the patient’s satisfaction and exercise compliance were evaluated using a 5-point Likert scale and percentage of exercise participation, respectively. Results At 3rd week, the ROM, SF-36, LKSS values, and pain scores were better in the participation group compared to the control group(p <.05). At 6th month, the IKDC, KOOS, SF-36 values and pain scores were also better in the participation group compared to the control group (p <.05). However, the ROM, LKSS, and TAS values were similar between groups at the 6th month(p >.05). Postop satisfaction at 3rd week and 6th month and exercise compliance postoperatively were significantly better in the participation group compared to the control group(p <.05). Conclusion Patient participation during ACLR surgery by communicating with the surgeon positively affects clinical and functional outcomes. It also contributes to patient satisfaction and compliance with the rehabilitation program postoperatively. Clinical trial number Not Applicable.